3D spin-flop transition in enhanced 2D layered structure single crystalline TlCo2Se2. (3rd August 2016) - Jin, Z; Xia, Z-C; Wei, M; Yang, J-H; Chen, B; Huang, S; Shang, C; Wu, H; Zhang, X-X; Huang, J-W; Ouyang, Z-W
Abstract: The enhanced 2D layered structure single crystalline TlCo2 Se2 has been successfully fabricated, which exhibits field-induced 3D spin-flop phase transitions. In the case of the magnetic field parallel to the c -axis ( B // c ), the applied magnetic field induces the evolution of the noncollinear helical magnetic coupling into a ferromagnetic (FM) state with all the magnetization of the Co ion parallel to the c -axis. A striking variation of the field-induced strain within the ab -plane is noticed in the magnetic field region of 20–30 T. In the case of the magnetic field perpendicular to the c -axis ( B   ⊥   c ), the inter-layer helical antiferromagnetic (AFM) coupling may transform to an initial canted AFM coupling, and then part of it transforms to an intermediate metamagnetic phase with the alignment of two-up–one-down Co magnetic moments and finally to an ultimate FM coupling in higher magnetic fields. The robust noncollinear AFM magnetic coupling is completely destroyed above 30 T. In combination with the measurements of magnetization, magnetoresistance and field-induced strain, a complete magnetic phase diagram of the TlCo2 Se2 single crystal has been depicted, demonstrating complex magnetic structures even though the crystal geometry itself gives no indication of the magnetic frustration.